Legal Counseling on Cybercrime: Educating Students of State Vocational High School 2 Palangka Raya on Digital Offenses and Their Legal Protection - Indang Sulastri; Satriya Nugraha; Bulan Tri Hardianty Hasanah; Dea Ariesta (Pusat Riset dan Inovasi Nasional, 2025)
This community service activity was carried out by the Faculty of Law, University of Palangka Raya, at SMK Negeri 2 Palangka Raya as an effort to enhance legal awareness among students. The background of this program lies in the increasing legal issues related to digital crimes and the urgent need for students to understand their legal rights and obligations in everyday life. The rapid growth of digital technology has led to an increased risk of cybercrimes, such as online fraud, cyberbullying, and data privacy violations, which have significant implications for individuals, particularly students. The main objective of this activity is to provide students with a comprehensive understanding of cybercrime, misuse of information technology, and the importance of responsible behavior in using social media. The methods applied in this program include interactive lectures, group discussions, case studies, and role-playing simulations, which encouraged students to actively participate in the learning process. The results indicated that students were able to grasp the fundamentals of laws related to cybercrime, recognize the potential dangers of irresponsible technology use, and demonstrate improved critical attitudes in responding to possible legal issues in daily activities. Furthermore, the program strengthened collaboration between the academic environment and vocational schools in building a young generation with strong legal awareness. In conclusion, interactive-based legal counseling proved effective in fostering legal awareness values among students, helping them make informed decisions in their digital interactions